Modeling systemic autoimmune rheumatic disease in rats under the adverse weather conditions - Yegudina Ye.D.; Synyachenko О.V.; Khanyukov О.О.; Suiarko V.І.; Тaktashov G.S. (Medičnì Perspektivi)
Changes in the lungs, heart and kidneys are found in all animals with experimental systemic autoimmune rheumatic disease and respectively in 47%, 47% and 40% of cases of intact rats in a hostile environment with xenobiotics air pollution (ammonia + benzene + formalin), herewith in every third or fourth individual lesions of visceral vessels developed. The negative environmental situation increases the frequency of morphological signs of the disease, such as proliferation of endothelial vessels of the heart by 68% and renal arterioles by 52%, in addition, there are direct correlations of angiopathy degree in individual organs; this depends on the nature of pathological process modeling and demonstrates air pollution as a risk factor of disease in humans. The impact of pulmonary vessels sclerosis on the development of bronhosclerosis, perivascular infiltration of the heart muscle on the lymphocyte-macrophage infiltration of the stroma of the myocardium and sclerosis of renal arterioles on the degree of nephroslerosis of stroma is directly associated, with the model of systemic autoimmune rheumatic diseases whereas air pollution by xenobiotics determines dependences of the degree of cellular infiltration of alveolar septa from perivascular pulmonary infiltration, the development of cardiomyocytes hypertrophy from proliferation of the heart endothelial vessels, increase of kidney mesangial matrix from the proliferation of endothelial glomerular capillaries.